Hotel housekeeping: basic - Aruna Singh ([Place of publication not identified] : [Publishers name not idntified], 2020)
This book of Hotel Housekeeping provides knowledge on general Operations and Management, continues its endeavour to provide a comprehensive text to students of certificate , ITI, diploma, undergraduate, and postgraduate courses in hotel management
Keywords: Housekeeping; Hotel